PEMBERIAN TANAH : KOMPOS TANDAN KOSONG KELAPA SAWIT (TKKS) ; PUPUK NPK 16:16:16 TERHADAP PERTUMBUHAN BIBITKELAPA SAWIT (Elaeis guineensis Jacq.) di MAIN–NURSERY - Yuninda, Didi Eko; Bustari Badal; Yonny Arita Taher (Jurnal Research Ilmu Pertanian, 2021)
Research "Providing Soil, Oil Palm Empty Bunches Compost (TKKS); NPK Fertilizer 16:16:16 on the Growth of Oil Palm Seeds (Elaeis guineensis Jacq) ”has been implemented in Koto Panjang  Village, Ikur Koto, Koto Tangah District, Padang City. Starting from February to May 2020, the study aims to obtain the best comparison of soil planting media, OPEFB compost and NPK 16:16:16 fertilizer on the growth of oil palm seedlings. The design used was a completely randomized design (CRD), with 7 treatments and 4 replications. As treatment is the ratio of Soil: TKKS and NPK 16:16:16, namely: Treatment A = Soil + 5gr NPK, B = Soil: EFB (1: 1) + 5gr NPK, C = Soil: EFB (1: 1) + 10gr NPK, D = Land: TKKS (2: 1) + 5gr NPK, E = Land: TKKS (2: 1) + 10gr NPK, F = Land: TKKS (3: 1) + 5gr NPK, G = Land: TKKS ( 3: 1) + 10gr NPK. Based on the results of the research, it can be concluded that the provision of land: OPEFB compost; NPK Fertilizer 16:16:16 gave a very significant effect on plant height, weevil diameter, root fresh weight, root dry weight, fresh weight of stems, dry weight of stalks and not significantly different on the number of leaf midribs. Providing soil: The best OPEFB compost is found in treatment D = Soil: EFB (2: 1) + 5gr NPK.